1981
DOI: 10.1002/ajpa.1330550403
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size and morphology in a recent Australian Aboriginal population from Broadbeach, South East Queensland

Abstract: Odontometric and morphologic observations were made of the dentition of skeletal remains of australian aborigines from Broadbeach, S.E. Queensland. Tooth size, especially of the molars, was found to be significantly larger than that reported for other recent Aboriginal populations. Tooth morphology also differed, with a higher frequency of five cusped second molars, and a lower frequency of shoveling and Carabelli's cusp than previously reported as typical of Australian aborigines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…In addition to the samples previously described by the present author (T. Hanihara, 1989aHanihara, ,b,c, 1990aHanihara, ,b,c, 1991a, this study includes data for some groups of Australian Aborigines reported by various authors (K. Hanihara, 1976;Richards and Tefler, 1979;Smith et al, 1981;Townsend et al, 1990;Turner, 1990). A list of the samples recorded by the present author is given in Table 1.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to the samples previously described by the present author (T. Hanihara, 1989aHanihara, ,b,c, 1990aHanihara, ,b,c, 1991a, this study includes data for some groups of Australian Aborigines reported by various authors (K. Hanihara, 1976;Richards and Tefler, 1979;Smith et al, 1981;Townsend et al, 1990;Turner, 1990). A list of the samples recorded by the present author is given in Table 1.…”
Section: Methodsmentioning
confidence: 89%
“…The left side of these figures is based on my own data. The right side gives the frequencies of the traits for Australian Aborigines reported by other workers (K. Hanihara, 1976;Richards and Tefler, 1979;Smith et al, 1981;Townsend et al, 1990;Turner, 1990).…”
Section: Balakrishnan and Sanghvimentioning
confidence: 89%
“…Another method, assuming the threshold mechanism, has dichotomized the non-metric dental traits into present and absent groups to view dental traits as entities. 20,31,32,[39][40][41][42][43] On the basis of these prior studies, dichotomization reduces possible classificat i o n bias and has another trait entity significance.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are comparable to the frequency observed in the Japanese sample of the present study. Smith (1981) reported the frequency of this trait in a recent Australian aboriginal population as 64.0%. This figure, falling in the range of the Pacific populations shown in this study, may indicate close relationship between Australian Aboriginals and other Pacific populations.…”
Section: Discussionmentioning
confidence: 97%